The influence of face mask on social spaces depends on the behavioral immune system - Geers, Laurie; Coello, Yann (Frontiers in Neuroscience, 2022)
Interacting with objects and people requires specifying localized spaces where these interactions can take place. Previous studies suggest that the space for interacting with objects (i.e., the peripersonal space) contributes to defining the space for interacting with people (i.e., personal and interpersonal spaces). Furthermore, situational factors, such as wearing a face mask, have been shown to influence social spaces, but how they influence the relation between action and social spaces and are modulated by individual factors is still not well understood. In this context, the present study investigated the relationship between action peripersonal and social personal and interpersonal spaces in participants approached by male and female virtual characters wearing or not wearing a face mask. We also measured individual factors related to the behavioral immune system, namely willingness to take risks, perceived infectability and germ aversion. The results showed that compared to peripersonal space, personal space was smaller and interpersonal space was larger, but the three spaces were positively correlated. All spaces were altered by gender, being shorter when participants faced female characters. Personal and interpersonal spaces were reduced with virtual characters wearing a face mask, especially in participants highly aversive to risks and germs. Altogether, these findings suggest that the regulation of the social spaces depends on the representation of action peripersonal space, but with an extra margin that is modulated by situational and personal factors in relation to the behavioral immune system.